2007
DOI: 10.1007/s00192-007-0449-y
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of TVT operations in 1,113 women with mixed urinary incontinence at 7 and 38 months

Abstract: A follow-up was done 7 and 38 months after tension-free vaginal tape (TVT) operation in 1,113 women with mixed urinary incontinence. Mixed incontinence and predominant bother were subjectively defined. The results were analyzed according to the women's predominant bother: stress incontinence, urge incontinence, or stress and urge incontinence equally. Across the groups, stress incontinence was cured in 87 and 83% of the women at 7 and 38 months, respectively, with no difference between the three groups. Women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 20 publications
3
41
1
3
Order By: Relevance
“…Furthermore, a resent study confirmed the cure rate after TVT procedure better in women with predominant stress incontinence and those with stress and urge incontinence equally than those with predominant urge incontinence [22]. Our study confirms that the success rate is considerably better in patients who undergo TOT for genuine SUI than for MUI.…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, a resent study confirmed the cure rate after TVT procedure better in women with predominant stress incontinence and those with stress and urge incontinence equally than those with predominant urge incontinence [22]. Our study confirms that the success rate is considerably better in patients who undergo TOT for genuine SUI than for MUI.…”
Section: Discussionsupporting
confidence: 79%
“…The significance of the urgency incontinence component in MUI women on surgical results after TVT has also been verified in a study from KulsengHanssen et al from 2008 (52).…”
Section: Paper IImentioning
confidence: 76%
“…A score of 0 indicates no incontinence, while the highest scores mean that the woman experiences leakage so severe that urine runs down her legs more than once every day. Women with a score below 3 on either index have essentially the same incontinence-related quality of life as normal control women without incontinence [18].…”
Section: Introductionmentioning
confidence: 75%